Comparison of forced-choice and subjective probability scales measuring behavioral intentions. - Flannelly, Laura T.; Flannelly, Kevin J.; McLeod, Malcolm S. (Psychological Reports, 2000)
Three surveys compared the accuracy of predictions based on forced-choice and subjective probability scales. The latter produced significantly more accurate election predictions and significantly reduced the percentage of undecided, or “Don't Know” responses, compared to forced-choice scales in all three surveys. Analysis indicates subjective probability scales decrease sampling error and confirms there is an inherent source of error in traditional forced-choice questions about voting intentions not attributable to sampling error. The results are discussed with respect to (1) sampling and measurement errors in forced-choice and subjective probability scales measuring behavioral intentions, (2) their practical application, and (3) cognitive theory, especially support theory. Reprinted by permission of the publisher, 2000.